Problems of adapting lecture halls of Lublin University of Technology to modern utility needs - Kwiatkowski, Bartłomiej; Pinkovskyi, Kostiantyn; Lozovskyi, Pavlo (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2024)
This article presents the problems associated with the adaptation and adjustment of lecture halls to modern requirements on the example of selected departments of Lublin University of Technology. Lecture classes are intended for the largest audience which results in numerous functional and legal requirements related to the adaptation of these spaces. The authors of the text analyze the problem of adapting seminar spaces in the existing buildings of the various faculties located on the campus of Lublin University of Technology. Functional, utilitarian and technical aspects are analyzed, as well as the problems arising from the current construction law. Lectures are the primary form of transferring theoretical knowledge during the course of study. In addition, lecture halls are used as venues for training courses, scientific conferences and faculty seminars. Such a wide range of uses requires adapting them to the needs of a wide range of users. As a result of their research, the authors present problems and design solutions in the process of arranging seminar spaces.